Visual Identity and Packaging Design for Gringsing Textile Products from Bali Morinda Art Textile SME at BEDA’KAN 8th Batch - Aurellia, Medelyn; Hananto, Brian Alvin (de-lite: Journal of Visual Communication Design Study & Practice, 2022)
Morinda Art Textile is one of the SMEs (Small Medium Enterprise) that sells Gringsing textile products and is located in Bali, Indonesia. Gringsing is a typical textile that is quite old and very well-known in Bali. This project was done for a program called BEDA'KAN in the 8th batch. The Ministry of Tourism and Creative Economy in Indonesia initiated this program. The packaging design for Morinda Art Textile was carried out using the Eric Karjaluoto methodology. This design was carried out in November 2021 and ended in December 2021.